2016
DOI: 10.15237/gida.gd16013
|View full text |Cite
|
Sign up to set email alerts
|

Et Kaynakli Bi̇yoakti̇f Pepti̇tler Ve Fonksi̇yonel Özelli̇kleri̇

Abstract: Et kreatin, taurin, konjuge linoleik asit (KLA) ve peptitler gibi pek çok biyoaktif bilefleni içermektedir. Peptitler son y›llarda üzerine fazla say›da çal›flma yap›lan biyoaktif bileflenlerdendir. Biyoaktif özellik gösteren peptitler 2-30 aras›nda aminoasit içeren k›sa zincirli ve düflük molekül a¤›rl›kl› bir yap›ya sahiptir. Biyoaktif peptitler, antimikrobiyel, antitrombotik, hipokolesterolemik, antioksidan, opioid ve ba¤›fl›kl›k sistemini düzenleyici etkilerinden dolay› canl› vücudunda çok önemli roller üst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…1c). Şimşek and Artık [5] reported that in 25 grape molasses, the total ash among 3.57-3.83%. Some minerals as mg per 100g such as K, Ca, Mg, P, Na, Fe, Zn, Cu and, Mn determined between 885-978, 124-139, 67-81, 74-87, 30-37, 13.6-15.8, 0.11-0.14, 0.35-0.44, 0.56-0.72 respectively.…”
Section: Microelementsmentioning
confidence: 99%
See 1 more Smart Citation
“…1c). Şimşek and Artık [5] reported that in 25 grape molasses, the total ash among 3.57-3.83%. Some minerals as mg per 100g such as K, Ca, Mg, P, Na, Fe, Zn, Cu and, Mn determined between 885-978, 124-139, 67-81, 74-87, 30-37, 13.6-15.8, 0.11-0.14, 0.35-0.44, 0.56-0.72 respectively.…”
Section: Microelementsmentioning
confidence: 99%
“…Molasses with naturally rich sugar composition is another food with a high energy value as hazelnuts. Grape molasses is traditional nutrition, rich in sugar (glucose 30-35.0%, fructose 30-34.4%) and minerals (K, P, Ca, Mg, Fe, Mn, Cu, Zn) produced by ltration and evaporation of aqueous extracts of dried fruit or fresh fruit without using any additives or added sugar [5].…”
Section: Introductionmentioning
confidence: 99%
“…Cys-Cys ve Cys-Arg ACE inhibitör dipeptitlerdir. ACE kan basıncının düzenlenmesinde rol alan bir enzimdir [8]. Gao [11].…”
unclassified